A phase 2 study to assess the pharmacokinetics and pharmacodynamics of CPX-351 and its effects on cardiac repolarization in patients with acute leukemias - Lin, Tara L. (Cancer Chemother Pharmacol, 2019)
PURPOSE: Daunorubicin can induce left ventricular dysfunction and QT interval prolongation. This study assessed the effects of CPX-351, a liposomal encapsulation of cytarabine and daunorubicin, on cardiac repolarization. METHODS: Twenty-six adults with acute leukemia were treated with CPX-351 for 1–2 induction cycles and ≤ 4 consolidation cycles. The primary endpoint was mean change in QTcF from baseline. RESULTS: Mean QTcF changes were < 10 ms at all time points. No clinically meaningful effects on heart rate, QRS interval, PR interval, or QTcB were observed. Estimated mean half-lives for total cytarabine and daunorubicin were > 30 h. Thirteen (50%) patients achieved remission. The most common adverse events were febrile neutropenia, fatigue, and nausea. CONCLUSIONS: The cytarabine and daunorubicin in CPX-351 liposomes were metabolized and excreted similarly to conventional formulation; however, plasma pharmacokinetics were altered. CPX-351 did not prolong the QT interval, suggesting that CPX-351 may induce less cardiotoxicity than previously reported for conventional daunorubicin. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT02238925. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00280-019-03856-9) contains supplementary material, which is available to authorized users.